2018
DOI: 10.4103/liuj.liuj_4_18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of micronization on the physical properties of salbutamol sulfate as a model drug used in dry powder inhalation

Abstract: Purpose: Investigation of the crystallinity of salbutamol sulfate a model drug used in the dry powder inhalation formulation. Materials and Methods: Salbutamol sulfate was supplied kindly by Lindopharm (Hilden, Germany). Salbutamol sulfate was milled using an air jet milling process, the particle size and morphology were determined using laser diffraction and the scanning electron microscopy. The drug was subjected to conditioning through storage at 52.8% and 75% relative humidity for 24 h, 1 week, and 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Using isothermal microcalorimetry it was observed that the micronized revatropate hydrobromide recrystallized at RH >30% [48]. Boshhiha et al made a similar observation on salbutamol [49]. They found that amorphous regions can be generated in crystalline materials during the jet milling process, which had significant impacts on physical stability [49].…”
Section: Millingmentioning
confidence: 91%
See 2 more Smart Citations
“…Using isothermal microcalorimetry it was observed that the micronized revatropate hydrobromide recrystallized at RH >30% [48]. Boshhiha et al made a similar observation on salbutamol [49]. They found that amorphous regions can be generated in crystalline materials during the jet milling process, which had significant impacts on physical stability [49].…”
Section: Millingmentioning
confidence: 91%
“…Boshhiha et al made a similar observation on salbutamol [49]. They found that amorphous regions can be generated in crystalline materials during the jet milling process, which had significant impacts on physical stability [49]. Thus, re-crystallization of the amorphous regions can lead to changes in the physico-chemical properties of the micronized particles and formation of strong agglomerates, which has the potential to significantly impact the aerosol performance of the formulation [50,51,52].…”
Section: Millingmentioning
confidence: 92%
See 1 more Smart Citation